PEMBELAJARAN MENULIS TEKS EKSPOSISI DI KELAS VII SMP NEGERI 1 GEDONGTATAAN - Oriza Pratiwi; Nurlaksana Eko Rusminto; Mulyanto Widodo (FKIP Universitas Lampung, 2013)
The problem presented in this research was the learning process of writing exposition text by grade VII students at SMP Negeri 1 Gedongtataan in academic year of 2013/2014. Based on the problem above, the objective of this research was to describe the learning process of writing exposition text including planning, implementation, and evaluation. Based on this research, lesson plans designed by the teachers have fulfilled the criteria of specified lesson plan. However, there are some weaknesses in formulating learning assessment. Implementation of learning that form of teacher activity in the classroom consists of preliminary activities, core activities, and closing activities. Students activities in implementation of learning writing exposition text consists of observing, questioning, associating and communicating. Assessments of students' learning outcomes done by the teacher are assessment of attitudes, knowledge, and skill.Masalah dalam penelitian ini adalah proses pembelajaran menulis teks eksposisi kelas VII SMP Negeri 1 Gedongtataan tahun pelajaran 2013/2014. Berdasarkan masalah tersebut, penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran menulis teks eksposisi meliputi perencanaan, pelaksanaan, dan evaluasi pembelajaran. Berdasarkan hasil penelitian, perencanaan pembelajaran yang dirancang oleh guru sudah memenuhi kriteria Rencana Pelaksanaan Pembelajaran yang ditentukan. Namun, masih terdapat kekurangan pada perumusan penilaian pembelajaran. Pelaksanaan pembelajaran yang berupa aktivitas guru dalam kelas terdiri atas kegiatan pendahuluan, kegiatan inti, dan kegiatan penutup. Aktivitas siswa dalam pelaksanaan pembelajaran menulis teks eksposisi terdiri atas aktivitas mengamati, menanya, menalar, dan mengomunikasikan. Penilaian hasil belajar siswa yang dilakukan oleh guru ialah penilaian sikap, pengetahuan, dan keterampilan.Kata kunci: menulis, pembelajaran, teks eksposisi.